2019
DOI: 10.1111/plb.12983
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic trajectories of volatile and non‐volatile specialised metabolites in ‘overnight’ fragrant flowers of Murraya paniculata

Abstract: Ephemeral flowers, especially nocturnal ones, usually emit characteristic scent profiles within their post‐anthesis lifespans of a few hours. Whether these flowers exhibit temporal variability in the composition and profile of volatile and non‐volatile specialised metabolites has received little attention. Flowers of Murraya paniculata bloom in the evenings during the summer and monsoon, and their sweet, intense fragrance enhances the plant's value as an ornamental. We aimed to investigate profiles of both vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 68 publications
(77 reference statements)
1
13
0
Order By: Relevance
“…The findings of our result also correspond well with the findings of other summer jasmines where the maximum emission was observed at late night on the same day of flower blooming (Bera et al, 2017;Pragadheesh et al, 2017;Yu et al, 2017). These findings show that this species is nocturnally active to attract night pollinators (Paul et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of our result also correspond well with the findings of other summer jasmines where the maximum emission was observed at late night on the same day of flower blooming (Bera et al, 2017;Pragadheesh et al, 2017;Yu et al, 2017). These findings show that this species is nocturnally active to attract night pollinators (Paul et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Several floral volatile compounds are stored in vacuoles as water soluble glycosides (Watanabe et al, 1993;Barman and Mitra, 2019), upon physiological necessity, these compounds are cleaved by hydrolytic enzymes and subsequently released as fragrant molecules from floral tissue (Reuveni et al, 1999). In the past decades, a range of scent compounds were identified in many scented flowers such as,Rosa, (Helsper et al, 1998;Hendel-Rahmanim et al, 2007),Petunia (Schuurink et al, 2006), Antirrhinum (Kolosoba et al, 2001), Matricaria (Irmisch et al, 2012), Clarkia (Raguso and Pichersky, 1995), Murraya (Paul et al, 2019). Further, essential oils extracted from various scented flowers were reported to possess many pharmacological values (Kuroda et al, 2005;Wei and Shibamoto., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These temporary reservoirs, whether they are produced in the plant cell (e.g., plastids, cytosol, in association with cell membranes) or stored (e.g., resin ducts), must diffuse through aqueous phases in the mesophyll, a complex series of lipid bilayer membranes and internal air spaces, before they are emitted to the atmosphere (Cheng et al, 2016). Therefore, floral volatile blends are correlated with the plant physiological state, both at the level of the internal volatile pool and the emitted blend (Loreto et al, 1996;Paul et al, 2019;Kutty et al, 2021). We specifically found that water shortage decreased the amounts of volatiles in the plants, and increased the amounts of volatiles under whitefly infestation.…”
Section: F I G U R E 5 a Venn Diagram Of Volatiles Detected In Blends Ofmentioning
confidence: 99%
“…Methodologically, it is important to note that although the bumblebee response was based only on the volatiles that are actively emitted from the plants, as in nature, we used a more thorough analysis of volatile composition when studying the floral volatile blends. However, because studies have shown that the results of the two techniques are comparable for several volatile compounds, we preferred to use the most suitable method for each part of the study (Paul et al, 2019;Kutty et al, 2021). The olfactometer assay, in which the bumblebees had no visual or physical contact with the plants, clearly indicated that these pollinators preferred the floral blends of the less stressed M. livida plants in any of the combinations.…”
Section: F I G U R E 5 a Venn Diagram Of Volatiles Detected In Blends Ofmentioning
confidence: 99%
“…Gelsemiaceae (Z)-α-ocimene, α-farnesene [29] Gossypium hirsutum Malvaceae (3S)-linalool GhTPS12 [30,31] Jasminum spp. Oleaceae α-farnesene, linalool, β-ocimene, germacrene-D [32][33][34][35][36] Laurus nobilis Lauraceae sesquiterpenes, γ-cadinene, δ-cadinene [37] Lonicera japonica Caprifoliaceae linalool [38] Magnolia champaca Magnoliaceae (R)-linalool, linalool and its oxides [39] Malus domestica Rosaceae (E)-linalool oxide [40] Murraya paniculata Rutaceae E-β-ocimene, linalool, α-cubebene [41,42] Myrtus communis L. Myrtaceae α-pinene, linalool, 1,8-cineole [43] Osmanthus fragrans Oleaceae linalool and its derivatives, α-ionone, β-ionone OfTPS1, OfTPS2, OfTPS3 [44][45][46][47] Paeonia spp. Paeoniaceae β-caryophyllene, linalool [48,49] Psidium guajava Myrtaceae α-cadinol, β-caryophyllene, nerolidol [50] Rosa spp.…”
Section: Datura Wrightiimentioning
confidence: 99%